Kinetics and products of 4-aminotoluene oxidization by ozone in the liquid phase - Bushuyev, Andrey; Keremet, Michael; Galstyan, Andrey; Galstyan, Tatyana (Publishing House of Lviv Polytechnic National University, 2015)
The kinetic regularities and mechanisms of oxidation reactions of 4-aminotoluene and its acylation derivatives by the gases that contain ozone in the glacial acetic acid have been studied. The process of liquid-phase catalytic oxidation of 4-acetaminotoluene by ozone in the presence of transition metal salts and their mixtures with potassium bromide to the corresponding acetaminobenzoic acid has been investigated. Встановлені кінетичні закономірності та запропонований механізм реакцій окиснення 4-амінотолуену і його ацильованої похідної у крижаній оцтовій кислоті. Вивчено процес каталітичного рідиннофазного окиснення 4-ацетамі- нотолуену озоном у присутності солей перехідних металів та їх сумішей з калій бромідом.
Кінетика і продукти окиснення 4-амінотолуену озоном у рідкій фазі
Keywords: 4-acetaminotoluene; acetic acid; 4-aminotoluene; oxidization; ozone; 4-ацетамінотолуен; оцтова кислота; 4-амінотолуен; окиснення; озон